Rozpoznanie i leczenie łagodnych przypadków COVID-19 w warunkach domowych – wyzwania i ryzyka - Kocik, Janusz; Pinkas, Jarosław (Wiedza Medyczna, 2020)
The majority of subjects infected with SARS-CoV-2 virus will pass through the disease with mild symptoms. At the same time it seems that they are highly infectious. In the influenza-like illnesses season COVID-19 is one of the many that may cause similar symptoms. Waiting for triage and medical assessment in designated healthcare facilities the patients are endangered by additional contact with other dependent patients and healthcare personnel. With the surge wave of cases, designated healthcare facilities should take care of those who are genuinely endangered with an emerging severe respiratory distress. Patients with mild symptoms should be subject to testing, put into surveillance and treatment in home isolation. However, due to high transmissibility and severe course of COVID-19 in part of infected, the rules of transmission restriction to household members and community should be followed. The authors, following World Health Organization, present the guidelines for home care for COVID-19 patients with mild symptoms.